Taking connected mobile-health diagnostics of infectious diseases to the field. - Wood,CS; Thomas,M; Budd,J; Mashamba-Thompson,TP; Herbst,K; Pillay,D; Peeling,RW; Johnson,AM; McKendry,RA; Stevens,M (Nature, 2019)
Mobile Health or mHealth - The application of mobile devices, their componentsand related technologies to healthcare is improving patients’ access to treatment andadvice. Now, in combination with connected diagnostic devices it offers new possibilitiesto diagnose, track and control infectious diseases and improve health systemefficiencies. In this context we look at these technologies and highlight their promise butalso the challenges in realising their potential to increase patient access to testing, aid intheir treatment and improve the capability of public health authorities to monitoroutbreaks, implement responses, and assess the impact of interventions across theworld.